New challenges in sustainable development for russia and the world. (CAMBRIDGE SCHOLARS PUBLIS, 2018)
This volume offers profound analyses of the main theoretical and practical aspects of the concept of sustainable development: namely, current environmental problems; the building of green economies; climate policies; specifics of international cooperation in the sphere of sustainable development; specific features of business and government involvement in implementing sustainable development; the role of civil society; its social and gender aspects; and specific characteristics of national models of sustainable development. The focus on the international aspects of the implementation of sustai.